2019
DOI: 10.1002/tcr.201900085
|View full text |Cite
|
Sign up to set email alerts
|

Design of Advanced Functional Materials Using Nanoporous Single‐Site Photocatalysts

Abstract: Nanoporous silica solids can offer opportunities for hosting photocatalytic components such as various tetra‐coordinated transition metal ions to form systems referred to as “single‐site photocatalysts”. Under UV/visible‐light irradiation, they form charge transfer excited states, which exhibit a localized charge separation and thus behave differently from those of bulk semiconductor photocatalysts exemplified by TiO2. This account presents an overview of the design of advanced functional materials based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…With those catalysts, a catalytic reaction takes place as light hits titanium oxide (TiO 2 ). Universities and research institutes have been studying photocatalysts for about 50 years, and products applying this technology have already been developed in many fields [15,16,17]. On the other hand, there have been few scientific reports on air catalysts so far, and their effects are still unknown.…”
Section: Fig 3 Amount Of Atp Measurements In Each Roommentioning
confidence: 99%
“…With those catalysts, a catalytic reaction takes place as light hits titanium oxide (TiO 2 ). Universities and research institutes have been studying photocatalysts for about 50 years, and products applying this technology have already been developed in many fields [15,16,17]. On the other hand, there have been few scientific reports on air catalysts so far, and their effects are still unknown.…”
Section: Fig 3 Amount Of Atp Measurements In Each Roommentioning
confidence: 99%
“…When a semiconductor is brought near a grafted metal, it encounters these intense electric fields, leading to the rapid formation of e --h + pairs in the semiconductor. Such phenomena have been exploited successfully in films activated by sunlight by using Cu [45], Au [46][47][48], and Ag [49][50][51]. It is worth noting that the electromagnetic near field at the plasmon resonance decreases rapidly, within 100 nm [52] from the plasmonic metal surface, effectively promoting surface reactions rather than generating charge carriers in the bulk of the material.…”
Section: Surface Graftingmentioning
confidence: 99%
“…This study employed pure SBA-15 as a support material. In another strategy, an Ag-based plasmonic catalyst was supported on Ti-containing mesoporous sili-ca 23), 24) . X-ray photoelectron spectroscopy (XPS) analysis confirmed that the binding energies of Ag shifted towards lower values by the incorporation of isolated and tetrahedrally coordinated single-site Ti-oxide moieties.…”
Section: (B))mentioning
confidence: 99%